Capillary electrophoretic study of green fluorescent hollow carbon nanoparticles. Issue 17 (3rd August 2015) - Liu, Lizhen; Feng, Feng; Hu, Qin; Paau, Man Chin; Liu, Yang; Chen, Zezhong; Bai, Yunfeng; Guo, Fangfang; Choi, Martin M. F.
<x xml:space="preserve">Abstract</x> CE coupled with laser‐induced fluorescence and UV absorption detections has been applied to study the complexity of as‐synthesized green fluorescent hollow carbon nanoparticles (HC‐NP) samples. The effects of pH, type, and concentration of the run buffer and SDS on the separation of HC‐NP are studied in detail. It is observed that phosphate run buffer is more effective in separating the HC‐NP and the optimal run buffer is found to be 30 mM phosphate and 10 mM SDS at pH 9.0. The CE separation of this HC‐NP is based on the difference in size and electrophoretic mobility of HC‐NP. Some selected HC‐NP fractions are collected and further characterized by UV‐visible absorption and photoluminescence (PL) spectroscopy, MS, and transmission electron microscopy. The fractionated HC‐NP show profound differences in absorption, emission characteristics, and PL quantum yield that would have been otherwise misled by studying the complex mixture alone. It is anticipated that our CE methodology will open a new initiative on extensive studies of individual HC‐NP species in the biomedical, catalysis, electronic, and optical device, energy storage, material, and sensing field.